The Oxford handbook of management / edited by Adrian Wilkinson, Steven J. Armstrong, and Michael Lounsbury. - Wilkinson, Adrian, 1963-; Armstrong, Steven J.; Lounsbury, Michael (Oxford University Press, 2017)
This handbook analyses and explores the evolution of management; the core functions and how they may have changed; its position in the culture of modern society; the institutions and ideologies that support it; and likely challenges and changes in the future.
Keywords: Management.